2016
DOI: 10.1007/s12028-016-0321-3
|View full text |Cite
|
Sign up to set email alerts
|

Perihematomal Edema Expansion Rates and Patient Outcomes in Deep and Lobar Intracerebral Hemorrhage

Abstract: Background and Purpose Perihematomal edema (PHE) expansion rate may predict functional outcome following spontaneous intracerebral hemorrhage (ICH). We hypothesized that the effect of PHE expansion rate on outcome is greater for deep versus lobar ICH. Methods Subjects (n=115) were retrospectively identified from a prospective ICH cohort enrolled from 2000–2013. Inclusion criteria were age ≥18 years, spontaneous supratentorial ICH, and known onset time. Exclusion criteria were primary intraventricular hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 34 publications
(55 reference statements)
1
42
2
1
Order By: Relevance
“…Edema in the peri‐hematoma region was detected from day 1 post‐ICH and was a consistent feature in all ICH cases. Our observation is consistent with peri‐hematoma edema reported from head scans of ICH patients within 1 day of the hemorrhage and in association with poorer outcome . Red neurons indicative of ischemic neuronal damage were present within the peri‐hematoma area in most (88%) of the subjects within 3 days of the ICH and up to 12 days post‐ICH.…”
Section: Discussionsupporting
confidence: 90%
“…Edema in the peri‐hematoma region was detected from day 1 post‐ICH and was a consistent feature in all ICH cases. Our observation is consistent with peri‐hematoma edema reported from head scans of ICH patients within 1 day of the hemorrhage and in association with poorer outcome . Red neurons indicative of ischemic neuronal damage were present within the peri‐hematoma area in most (88%) of the subjects within 3 days of the ICH and up to 12 days post‐ICH.…”
Section: Discussionsupporting
confidence: 90%
“…10 The latest prospective studies showed a strong relationship between PHHD volume and higher mortality and morbidity. 8,9,[33][34][35][36] This prognostic capacity is higher during the first 24 hours, progressively decreasing its value during the subacute phase of ICH. 9 Although the prognostic capacity of the PHHD volume over the clinical outcome was not the main objective of our study, we initially showed that PHHD volume was significantly higher in patients with a worse outcome at 3 months, and a PHHD volume <6 mL was 4 times more frequent in patients with a good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…6 Clinical trials aimed at halting hematoma growth have failed to show efficacy so far 7 and new therapeutic targets are being sought, now focusing on other secondary mechanisms associated with brain damage, such as the perihematomal hypodensity (PHHD) volume. [8][9][10] Hyperthermia has been associated with poor outcome in ICH 11 and with the increase of PHHD volume, 12 especially by hypertensive mechanisms. 13 Hypothermia has been proposed as a treatment for ICH that is associated with a decrease in PHHD.…”
mentioning
confidence: 99%
“…Cytotoxicity, excitotoxicity, oxidative stress and the in ammatory response, all of which can be induced following ICH, can lead to the destruction of the BBB [5]. One of the events following the disruption of BBB is brain edema, which adversely affect the outcome and prognosis of patients with ICH [6,32]. Therefore, protecting the integrity of the BBB is crucial for attenuating secondary brain injury following ICH.…”
Section: Discussionmentioning
confidence: 99%